Age, Height, and Sex on Motor Evoked Potentials: Translational Data From a Large Italian Cohort in a Clinical Environment - Cantone, Mariagiovanna; Lanza, Giuseppe; Vinciguerra, Luisa; Puglisi, Valentina; Ricceri, Riccardo; Fisicaro, Francesco; Vagli, Carla; Bella, Rita; Ferri, Raffaele; Pennisi, Giovanni; Di Lazzaro, Vincenzo; Pennisi, Manuela (Frontiers in Human Neuroscience, 2019)
Introduction: Motor evoked potentials (MEPs) to transcranial magnetic stimulation are known to be susceptible to several sources of variability. However, conflicting evidences on individual characteristics in relatively small sample sizes have been reported. We investigated the effect of age, height, and sex on MEPs of the motor cortex and spinal roots in a large cohort. Methods: A total of 587 subjects clinically and neuroradiologically intact were included. MEPs were recorded during mild tonic contraction through a circular coil applied over the “hot spot” of the first dorsal interosseous and tibialis anterior muscles, bilaterally. Central motor conduction time (CMCT) was estimated as the difference between MEP cortical latency and the peripheral motor conduction time by cervical or lumbar magnetic stimulation. Peak-to-peak MEP amplitude to cortical stimulation and right-to-left difference of each parameter were also measured. Results: After Bonferroni correction, general linear (multiple) regression analysis showed that both MEP cortical latency and peripheral motor conduction time at four limbs positively correlated with age and height. At lower limbs, an independent effect of sex on the same measures was also observed (with females showing smaller values than males). CMCT correlated with both age (negatively) and height (positively) when analyzed by a single regression; however, with a multiple regression analysis this significance disappeared, due to the correction for the multicollinearity within the dataset. Conclusions: Physical individual features need to be considered for a more accurate and meaningful MEPs interpretation. Both in clinical practice and in research setting, patients and controls should be matched for age, height, and sex.